New records of Meiothecium boryanum (Müll.Hal.) Mitt. (Sematophyllaceae, Bryophyta) in Brazil - Santos, Milena Evangelista dos (2022)
During the review of species of the Sematophyllaceae family deposited in national herbaria, it was possible to expand the occurrence record of Meiothecium boyanum (Müll.Hal.) Mitt. in Brazil. Currently, the confirmed occurrence of the species is limited to the States of Bahia, Goiás, Rio de Janeiro, Rio Grande do Sul and São Paulo, although only the State of Bahia is mentioned in Flora e Funga do Brasil 2022. With this work, the species had its record confirmed for Minas Gerais and Pernambuco States.